A Stochastic View of the 2020 Elazığ Mw 6.8 Earthquake (Turkey). Issue 3 (3rd February 2021) - Ragon, Théa; Simons, Mark; Bletery, Quentin; Cavalié, Olivier; Fielding, Eric
Abstract: Until the M w 6.8 Elazığ earthquake ruptured the central portion of the East Anatolian Fault (EAF, Turkey) on January 24, 2020, the region had only experienced moderate magnitude ( M w  < 6.2) earthquakes over the last century. We use geodetic data to constrain a model of subsurface fault slip. We adopt an unregularized Bayesian sampling approach relying solely on physically justifiable prior information and account for uncertainties in both the assumed elastic structure and fault geometry. The rupture of the Elazığ earthquake was mostly unilateral, with two primary disconnected regions of slip. This rupture pattern may be controlled by structural complexity. Both the Elazığ and 2010 M w 6.1 Kovancılar events ruptured portions of the central EAF that are believed to be coupled during interseismic periods, and the Palu segment is the last portion of the EAF showing a large fault slip deficit which has not yet ruptured in the last 145 years. Plain Language Summary: The Elazığ earthquake ruptured the central portion of the East Anatolian Fault (EAF), a major strike‐slip fault in eastern Turkey, on January 24, 2020. Before this event, the region had only experienced moderate magnitude earthquakes over the last century. We aim at understanding the rupture of this earthquake, and how it relates to the historical ruptures of the EAF. To do so, we use measurements of displacement at the surface to image the subsurface slip on the fault that occurred during the earthquake. As the characteristics of the crust are poorly known, we make realistic assumptions on the fault geometry and Earth structure, and build on novel approaches to account for the possible biases of our assumptions and to characterize the uncertainties of the imaged slip. We suggest that the Elazığ earthquake rupture may be controlled by structural complexity of the fault, and that two main regions of slip surround a fault bend acting as a barrier to rupture propagation. We also suggest that the fault segment located between Lake Hazar and the city of Palu is the last portion of the central EAF, showing a large deficit of the fault slip, which has not yet ruptured in the last 145 years. Key Points: We infer a stochastic model for the distribution of subsurface fault slip associated with the 2020 Elazığ earthquake We account for uncertainties in both the depth‐dependence of the assumed elastic structure and the location and geometry of the fault Our models are characterized by two primary patches of fault slip where distribution appears to be controlled by geometrical complexities